The relationship between tourist’s path selection and space image: A case study of peripheral lines surrounding the West Lake - X. M. Zhao; J. R. Shi; Y. Y. Duan; Y. X. Lei; K. Hokao (International Association of Lowland Technology, 2015)
Relationship between space image and tourists’ path selection patterns plays a very important role in landscape planning and design in scenic areas. Based on research of West Lake scenic area in Hang Zhou, this article studies the small scale space scenic images and big scale spatial structure images through questionnaire surveys, image recognition, image sketch, factor analysis, dynamic observation and other methods. The results indicate that there are four main types of space activities among the West Lake tourists, namely (1) the general activity type in the Bai Causeway and Su Causeway, (2) the general activity type in the Sunset Glow at Leifeng Pagoda, (3) the surrounding activity type in the Evening Bell at Nanping Hill, and (4) the surrounding activity type in the Music Fountain Square; and the proportion score has it in order from high to low. The score results of tourists' identifying picture and frequency of the five elements of space image in image maps are consistent with four main types of space activities observed by dynamic lines. Therefore, tourists' perception results of space image can directly affect the route choice behavior. And the more image elements can be perceived, the more reasonable path choices can be made. Finally, the research puts forward some suggestions tentatively on the planning and design of the West Lake area.